Territorial Strategic Planning as a support instrument for Regional and Local Development: a comparative analysis between Lisbon and Barcelona Metropolitan Areas - Marques, Bruno Pereira (2011)
MARQUES, B.P. (2011) "Territorial Strategic Planning as a support instrument for Regional and Local Development: a comparative analysis between Lisbon and Barcelona Metropolitan Areas", in Atas do 17.º Congresso da APDR, do 5.º Congresso de Gestão e Conservação da Natureza e do Congresso Internacional da APDR/AECR, Bragança e Zamora, pp. 1265-1272, ISBN 978-989-96353-2-6.